ENGLISH TEACHERS’ VOICES ON CURRICULUM CHANGE AND IMPLEMENTATION OF THE MERDEKA CURRICULUM IN RURAL JUNIOR HIGH SCHOOLS IN INDONESIA - JASRIAL, DEDI; SYARIF, HERMAWATI; ZAINIL, YETTI (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2023)
Curriculum changes are crucial in modern education to adapt to society's needs and technological advancements. Yet, rushed or poorly considered alterations might disrupt education's flow and harm students' learning and progress. Hence, this study explores rural Junior High School English teachers' voices on curriculum changes and the Merdeka curriculum implementation regarding curriculum aspects. Employing a qualitative approach with a case study design, five English teachers from rural schools in Bengkulu Province, Indonesia, were selected purposively. Semi-structured interviews were carried out to collect data and those data were analyzed using an interactive model. The findings of this study indicate teachers' positive reception to curriculum changes, benefiting both students and educators. The Merdeka Curriculum's implementation fulfilled various aspects, such as goals, resources, and teaching methods, yet encountered hurdles, like inadequate facilities, assessment system awareness, and learning module development. Despite successes, teachers expressed the necessity for training and workshops to effectively integrate the Merdeka curriculum into their teaching practices. In conclusion, rural English educators exhibit optimism toward the Merdeka Curriculum, appreciating its advantages while acknowledging challenges related to resource scarcity and the need for enhanced training in curriculum execution.